2021
DOI: 10.1111/ijcs.12752
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ motivations for adopting a vegan diet: A mixed‐methods approach

Abstract: The adoption of a vegan diet might have public, health, and environmental benefits; however, still little is known about veganism as the majority of studies on dietary lifestyles have focused on vegetarianism. Hence, in order to address this gap, the present study adopted a sequential and mixed (qualitative; quantitative) research approach based on laddering interviews (n = 20) and a survey (n = 400) to validate the motives for adopting a vegan diet. The results identified seven motives: economic, ethical, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 109 publications
(154 reference statements)
0
21
1
1
Order By: Relevance
“…To meat abstainers, the most important food choice motives are motives related to sustainability and health aspects: animal welfare, healthiness, food safety, environmental welfare, and naturalness. Studies by Malek and Umberger ( 33 ) and North et al ( 36 ) confirm that animal welfare is the most important motive for meat abstainers, and more specific for vegans ( 61 ), but contrary to our results, Malek and Umberger ( 33 ) show that for all dietary groups, price, and taste are among the five most important motives. Kemper et al ( 58 ) found that taste is a main reason for meat consumption while price is an important motive for meat reduction.…”
Section: Discussioncontrasting
confidence: 99%
“…To meat abstainers, the most important food choice motives are motives related to sustainability and health aspects: animal welfare, healthiness, food safety, environmental welfare, and naturalness. Studies by Malek and Umberger ( 33 ) and North et al ( 36 ) confirm that animal welfare is the most important motive for meat abstainers, and more specific for vegans ( 61 ), but contrary to our results, Malek and Umberger ( 33 ) show that for all dietary groups, price, and taste are among the five most important motives. Kemper et al ( 58 ) found that taste is a main reason for meat consumption while price is an important motive for meat reduction.…”
Section: Discussioncontrasting
confidence: 99%
“…Developing interventions to encourage lasting adoption of a vegan diet depends on understanding the psychological factors that determine why and for how long people attempt to switch to a vegan diet. Most research in this area has focused on reasons for switching; for example, many studies show that people typically choose to go vegan for health, environmental or ethical reasons (Ghaffari et al, 2021;Janssen et al, 2016;North et al, 2021; but see Cherry, 2015). However, an emphasis on motives for switching is problematic for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…For our methodological design, we used a mixed methods approach (qualitative and quantitative) (Ghaffari et al, 2022;Leech & Onwuegbuzie, 2009) to gain a deeper understanding of the acceptance of low-salt bread in the context of worksite canteens. The reformulated bread was the "B4 bread."…”
Section: Methodological Designmentioning
confidence: 99%